The Relative Position of the Solar Magnetic Dipole Axis and Rotation Axis of the Sun - Riehokainen, Alexandr; Smirnova, Victoria; Solov’ev, Alexander; Strekalova, Polina (MDPI AG, 2025)
We estimated the relative location of the solar rotation axis and the magnetic axis of the solar dipole, which were defined as centers of polar coronal holes. We used observations of polar coronal hole data, which were originally obtained with Solar Dynamic Observatory (SDO) spacecraft. To calculate the tilt of the magnetic axis relative to the rotation axis of the Sun, an empirical method for the estimation of the coronal hole centers is proposed. As a result, it was found that these axes do not coincide. The average deviation of the magnetic dipole axis from the rotation axis is ∼5 degrees of latitude. Using the wavelet transform method, it was found that the magnetic axis rotates around the rotation axis with a main period of 15–16 days. This period is related to the sector structure of the global magnetic field in the polar zones of the Sun.